Alibertia mahechae (Gardenieae, Rubiaceae), a new species from the Eastern Colombian Andes - Cortés-B., Rocio; Zapata-Correa, Diego A.; Persson, Claes; Delprete, Piero G. (Phytotaxa, 2024)
Alibertia mahechae (Gardenieae, Rubiaceae), a new tree species endemic to the forest of the Colombian Eastern Andes, is described and illustrated. The new species is distinguished by traits such as coriaceous, glabrous leaves, short stipules, pistillate flowers with 7–8-lobed corollas, and globose fruits with woody mesocarp. This new species is similar to A. occidentalis, from which it differs in the coriaceous leaf blades (vs. papyraceous in A. occidentalis), (5–)7–9 pairs of secondary veins [vs. 9–14(–16)], male flower with truncate calyx (vs. denticulate to slightly undulate), corolla tubes (15–)20–27 mm long (vs. 11–18 mm long), anthers 16–17.5 mm long (vs. 6.5–10 mm long), and female flower 7–8-merous (vs. 6-merous). A key to the Alibertia species occurring in Colombia is provided.